Peningkatan Kreativitas Guru PAUD Melalui Pelatihan Pengembangan Pembelajaran Anak Usia Dini dengan Pemanfaatan Media Loose Part - Nur Ismiatun, Asih; Siregar, Masyunita; Amnie, Erlida (Pendidikan Sejarah FKIP Universitas JAMBI, 2025)
This community ervice activity was carried out at Guang Ming Kindergarten, Jambi with the aim of increasing the creativity of early childhood education (ECE) teachers in developing early childhood learning by utilizing loose part media. The problems faced by partners are the need for understanding and practicing ECE learning activities due to the background of non-EEeducators and the creativity of teachers that needs to be improved. The implementation method uses lectures, questions and answers and training practices. The results of the activity showed an increase in teachers' abilities in compiling learning that is in accordance with the level of achievement of early childhood development and an increase in teacher creativity in compiling learning according to concrete and fun principles. Based on the evaluation results, teacher creativity assessed from four indicators (flexibility, originality, elaboration and fluency) increased by 80%. Furthermore, support for training opportunities and joint discussions to improve the creativity of ECE teachers must continue to be provided.